Molecular Dynamic Simulations Suggest That Metabolite-Induced Post-Translational Modifications Alter the Behavior of the Fibrinogen Coiled-Coil Domain - Sovova, Zofie; Suttnar, Jiri; Dyr, Jan E (Metabolites, 2021)
Fibrinogen is an abundant blood plasma protein that, inter alia, participates in blood coagulation. It polymerizes to form a fibrin clot that is among the major components of the thrombus. Fibrinogen reactions with various reactive metabolites may induce post-translational modifications (PTMs) into the protein structure that affect the architecture and properties of fibrin clots. We reviewed the previous literature to find the positions of PTMs of fibrinogen. For 7 out of 307 reported PTMs, we used molecular dynamics simulations to characterize their effect on the behavior of the fibrinogen coiled-coil domain. Interactions of the γ-coil with adjacent chains give rise to π-helices in Aα and Bβ chains of even unmodified fibrinogen. The examined PTMs suppress fluctuations of the γ-coil, which may affect the fibrinolysis and stiffness of the fibrin fibers. Citrullination of AαR104 and oxidations of γP70 and γP76 to glutamic semialdehyde unfold the α-helical structure of Aα and Bβ chains. Oxidation of γM78 to methionine sulfoxide induces the formation of an α-helix in the γ-coil region. Our findings suggest that certain PTMs alter the protein secondary structure. Thus, the altered protein structure may indicate the presence of PTMs in the molecule and consequently of certain metabolites within the system.
Keywords: oxidation; molecular dynamic simulation; post-translational modifications; fibrinogen; coiled-coil; citrullination